THE HERITAGE OF UZBEK FOLK MUSIC A CULTURAL TAPESTRY PRESERVED THROUGH GENERATIONS - Turdiyev Shavkat Akhmedovich (American Journals Publishing, 2024)
Uzbekistan, located in Central Asia, boasts a rich cultural heritage that is deeply intertwined with its music traditions. Uzbek folk music, with its diverse genres and distinctive features, serves as a window into the nation's history, traditions, and values. This article delves into the fascinating heritage of Uzbek folk music, exploring its origins, evolution, and enduring significance. Through an examination of traditional instruments, melodic patterns, lyrical themes, and performance contexts, we unravel the intricate tapestry of Uzbekistan's musical legacy and highlight the efforts taken to preserve and promote this cultural treasure.
Keywords: Uzbekistan, folk music, cultural heritage, Central Asia, traditional instruments, melodic patterns, lyrical themes, performance contexts, preservation, promotion